Patient's Satisfaction and Durability of Vertex Line Maxillary or Mandibular Complete Dentures - Nadira A Hatim; Mohammad A Mohi Al-Deen (University of Mosul, College of Dentistry, 2014)
The aims of this study were to evaluate the effect of lining maxillary or mandibular complete denture with different length of flange periphery with or without heat cured denture base material on the Patient's Satisfaction and Durability of VertexP®P Line materials. Materials and Methods: Twenty patients (11 Females, and 9 Males), age range 45-73 years with sever resorption completely edentulous arch (8 Patients) or arches (12 Patients) attend prosthodontic department clinic, College of Dentistry University of Mosul with complain of uncomfortable, soreness with previous prosthesis. All the participants were with history of extraction (8±2) years ago. Sixty four complete maxillary and mandibular dentures were constructed, (32) complete denture was done in conventional method and the other half maxillary and mandibular dentures were lined with VertexP®P (Heat cured liner), 2±0.5mm. of flange periphery without hard denture base material, and the other with 4±0.5mm. Each patient answers the Arabic version of (PDSQ) before and after insertion of the prosthesis and after 6months, and 12 months with follow up to 24months. Statistical analysis was done by using Mann-Whitney Test. Results: the results showed that a significant difference between gender, and significant differences between maxillary and mandibular denture for comfort. Durability factor showed significant differences with low percentage of patient comfort after 12 months (p≤0.05). Percentage of cracks in hard denture base flange materials was higher in mandibular denture with 4mm. vertex lined materials. Conclusions: Complete denture lined with VertexP®P heat cured material was more comfortable than conventional denture; Durability of this material was not more than 12 months. Vertex flange periphery should not more than 2±0.5mm